2016
DOI: 10.1088/0964-1726/25/7/075033
|View full text |Cite
|
Sign up to set email alerts
|

Improved resistive shunt by means of negative capacitance: new circuit, performances and multi-mode control

Abstract: This paper deals with vibration control by means of piezoelectric patches shunted with electrical impedances made up by a resistance and a negative capacitance. The paper analyses most of the possible layouts by which a negative capacitance can be built and shows that a common mathematical description is possible. This allows closed formulations to be found in order to optimise the electrical network for mono-and multi-mode control. General analytical formulations are obtained to estimate the performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
158
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(172 citation statements)
references
References 17 publications
(56 reference statements)
1
158
1
1
Order By: Relevance
“…In fact, it can be recalled that is a function of 2 (see (12)), and it can thus be modified by changing the geometrical, mechanical, and electrical characteristics of the actuator as well as its position [19]. Furthermore, can be also modified by connecting several piezoelectric actuators in series/parallel [25,26] and by using a negative capacitance [22,27]. Therefore, the model used here is of general validity.…”
Section: Attenuation Performance Of the Optimally Tuned Shuntmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, it can be recalled that is a function of 2 (see (12)), and it can thus be modified by changing the geometrical, mechanical, and electrical characteristics of the actuator as well as its position [19]. Furthermore, can be also modified by connecting several piezoelectric actuators in series/parallel [25,26] and by using a negative capacitance [22,27]. Therefore, the model used here is of general validity.…”
Section: Attenuation Performance Of the Optimally Tuned Shuntmentioning
confidence: 99%
“…The linear relationship demonstrated thus far (see (25) and (27)) can lead to the following notations:…”
Section: Attenuation Performance Of the Optimally Tuned Shuntmentioning
confidence: 99%
See 2 more Smart Citations
“…An important part of all calibration methods is the accurate determination of the squared EMCC, which governs both the attainable damping and the shunt tuning. Commonly, the squared EMCC is estimated from a single mode representation of the electromechanical structure (Thomas et al , 2009), while improved accuracy has been demonstrated by including quasi-static effects from higher non-resonant vibration modes (Berardengo et al , 2016). In other cases, the tuning is based directly on the squared effective EMCC determined from either experiments (Porfiri et al , 2007;Delperro et al , 2012) or by numerical analysis (Trindade and Benjeddou , 2009;Benjeddou , 2014).…”
Section: Introductionmentioning
confidence: 99%